The Antibacterial Synthetic Flavonoid BrCl-Flav Exhibits Important Anti-Candida Activity by Damaging Cell Membrane Integrity - Cornelia Babii; Mihaela Savu; Iuliana Motrescu; Lucian Mihail Birsa; Laura Gabriela Sarbu; Marius Stefan (MDPI AG, 2021)
Infections caused by Candida are very difficult to treat due to increasing antifungal resistance. Recent studies showed that patients with Candida infections resistant to fluconazole have very few treatment options. Therefore, finding new efficient antifungal agents is a matter of medical high priority. The aim of this study was to explore the antifungal potential of BrCl-flav-a representative of a new class of synthetic flavonoids with bromine as halogen substituent at the benzopyran core against four Candida clinical strains. Determination of minimum inhibitory concentration and minimum fungicidal concentration along with the time kill assay indicated a strong antifungal effect of BrCl-flav against C. albicans, C. parapsilosis, C. krusei and C. glabrata. The investigation of anti-Candida mechanism of action using fluorescence microscopy and scanning electron microscopy revealed that Br-Cl flav could inhibit fungal growth by impairing the membrane integrity, the resulting structural damages leading to cell lysis. BrCl-flav also showed important anti-virulence properties against Candida spp., inhibiting biofilm formation and yeast to hyphal transition. A strong synergistic antifungal effect against C. albicans strain was observed when BrCl-flav was used in combination with fluconazole. BrCl-flav has a good potential to develop new effective antifungal agents in the context of Candida spp. multidrug resistance phenomenon.